Active SMS-based surveillance of adverse events following immunisation with influenza and pertussis-containing vaccines in Australian pregnant women using AusVaxSafety. Issue 31 (26th June 2020) - Glover, Catherine; Crawford, Nigel; Leeb, Alan; Wood, Nicholas; Macartney, Kristine
Abstract: Background: Maternal immunisation is important to protect both mother and baby, but safety concerns can lead to low uptake. AusVaxSafety participant-based surveillance actively monitors adverse events following immunisation (AEFI) in Australia. We aimed to analyse AEFI in the days following vaccination with seasonal inactivated influenza vaccine (IIV) and/or reduced antigen diphtheria-tetanus-acellular pertussis vaccine (dTpa) in pregnant women in Australia. Methods: De-identified AEFI reports were solicited from vaccine recipients via automated SMS survey (using SmartVax software) following routine vaccination with IIV and/or dTpa at 219 national sentinel surveillance sites from 2015 to 2018. AEFI rates were compared by vaccine group (IIV alone, dTpa alone, or IIV and dTpa together), vaccine brand, trimester (IIV only) and vaccination period (April to August 2016–2018; IIV only). Women who had two vaccination encounters during surveillance were identified and AEFI rates compared for each dose. Results: Among 13, 758 participants, overall AEFI rates were lower following IIV (4.9%) than dTpa (6.4%) or IIV and dTpa given concomitantly (7.4%). The AEFI profile was similar for both vaccines, with injection site reactions, tiredness, and headache most commonly reported. Injection site pain and swelling/redness were significantly more common in women who received dTpa than IIV. Reports of medical attendance following immunisation were similar (0.3%) for each vaccine group. AEFI rates did not differ by IIV brand (FluQuadri®, Fluarix® Tetra), dTpa brand (Boostrix®, Adacel®), or by trimester. Among women with sequential dTpa vaccinations, 6.0% (7/116) had an AEFI following their second dTpa dose. Conclusions: Self-reported AEFI rates did not differ by trimester (IIV), or by vaccine brand (IIV or dTpa). Concomitant influenza and pertussis vaccination was associated with more frequent, but low rates of minor, expected AEFI. These real world 'citizen science-based' data provide further reassuring evidence of the safety of maternal vaccination.